2022
DOI: 10.5194/bg-2022-19
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Organic Matter Transformations are Disconnected Between Surface Water and the Hyporheic Zone

Abstract: Abstract. Biochemical transformations of organic matter (OM) are a primary driver of river corridor biogeochemistry, thereby modulating ecosystem processes at local to global scales. OM transformations are driven by diverse biotic and abiotic processes, but we lack knowledge of how the diversity of those processes varies across river corridors and across surface and subsurface components of river corridors. To fill this gap we quantified the number of putative biotic and abiotic transformations of organic mole… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In brief, the transformation analysis allows researchers to identify potential reactions by first looking at the mass difference between all peaks within a sample, and then comparing these differences to a list of common and known reactions. Recent research has demonstrated that results from this analysis are significantly related to ecosystem biogeochemistry (Graham et al, 2018;Buser-Young et al, 2023) and provide insight into both biotic and abiotic processes (Fudyma et al, 2021;Stegen et al, 2022). Given that these transformations are inherently tied to DOM composition changes, we suspect that the number of transformations within a sample should be related to the functional diversity of that sample (e.g., functional diversity calculated using H/C measures degradation state while transformations also partially estimate degradation may be significantly related).…”
Section: Introductionmentioning
confidence: 98%
“…In brief, the transformation analysis allows researchers to identify potential reactions by first looking at the mass difference between all peaks within a sample, and then comparing these differences to a list of common and known reactions. Recent research has demonstrated that results from this analysis are significantly related to ecosystem biogeochemistry (Graham et al, 2018;Buser-Young et al, 2023) and provide insight into both biotic and abiotic processes (Fudyma et al, 2021;Stegen et al, 2022). Given that these transformations are inherently tied to DOM composition changes, we suspect that the number of transformations within a sample should be related to the functional diversity of that sample (e.g., functional diversity calculated using H/C measures degradation state while transformations also partially estimate degradation may be significantly related).…”
Section: Introductionmentioning
confidence: 98%
“…To conduct this study, we analyzed previously published data from the WHONDRS Summer 2019 Sampling (S19S) campaign (Stegen et al, 2018) using unsupervised and supervised ML approaches to identify the environmental parameters influencing the diversity of DOM clusters (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The samples we analyzed were collected and processed in 2019 as part of the WHONDRS consortium (Stegen et al, 2018), and the data were retrieved from publicly available data packages Toyoda et al, 2020). Full details on sample and metadata collection are provided in Garayburu-Caruso et al (2020).…”
Section: Data Sourcesmentioning
confidence: 99%